2014
DOI: 10.1037/a0037157
|View full text |Cite
|
Sign up to set email alerts
|

Ecological momentary assessment of acute alcohol use disorder symptoms: Associations with mood, motives, and use on planned drinking days.

Abstract: Several theories posit that alcohol is consumed both in relation to one’s mood and in relation to different motives for drinking. However, there are mixed findings regarding the role of mood and motives in predicting drinking. Ecological momentary assessment (EMA) methods provide an opportunity to evaluate near real-time changes in mood and motives within individuals to predict alcohol use. In addition, endorsement of criteria of an alcohol use disorder (AUD) may also be sensitive to changes within subjects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
156
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(173 citation statements)
references
References 56 publications
16
156
1
Order By: Relevance
“…Although both theory and research assert drinking motives to be proximal antecedents to the decision to drink alcohol (Dvorak, Pearson, & May, 2014), the relationship between depressive symptoms and rumination is likely bidirectional (see Watkins, 2008 for a review). Thus, the temporal ordering of these variables cannot be demonstrated with cross-sectional survey data alone.…”
Section: Discussionmentioning
confidence: 99%
“…Although both theory and research assert drinking motives to be proximal antecedents to the decision to drink alcohol (Dvorak, Pearson, & May, 2014), the relationship between depressive symptoms and rumination is likely bidirectional (see Watkins, 2008 for a review). Thus, the temporal ordering of these variables cannot be demonstrated with cross-sectional survey data alone.…”
Section: Discussionmentioning
confidence: 99%
“…Since the goal of this study was to understand influences on sexual risk behavior (which was assessed via the morning assessment), we chose a 100 % target response rate for these assessments to maximize the availability of data on sex events. We chose an 80 % target response rate for random prompts to minimize missing data and align with similar benchmarks used in past EMA research [4245]. Several procedures were implemented by RAs to help participants achieve these response rates, including: (1) building rapport, (2) soliciting buy-into the study (e.g., conveying the importance of the data to understanding behavior, asking for their investment), (3) discussing strategies that can enhance response rates/quality (e.g., “get into a routine, make sure the ringer volume is high, keep the phone with you whenever possible”), and (4) emphasizing confidentiality of responses.…”
Section: Methodsmentioning
confidence: 99%
“…Research, particularly in college students, supports the assertion that some young adults drink to regulate their mood. For example, researchers found that daytime negative affect predicted subsequent drinking later that night (Dvorak, Pearson, & Day, 2014), while others found that more frequent changes in mood, specifically negative moods, predicted higher general levels of drinking to cope (Gottfredson & Hussong, 2013). Drinking to cope may reinforce the belief that alcohol is effective for regulating negative affect which can further contribute to the development of an AUD (Rousseau, Irons, & Correia, 2011).…”
Section: Introductionmentioning
confidence: 99%